GENERAL CONDITIONS OF PRODUCTION AND THE FEASIBILITY OF INSTALLING THE EXPORT PROCESSING ZONE (EPZ) OF CÁCERES, MATO GROSSO - Cruz, Jean da Silva [UNESP]; Hespanhol, Antonio Nivaldo [UNESP] (Univ Estado Rio Janeiro, 2024)
This article analyzes the General Production Conditions (GPC) and their role in the feasibility of installing the Export Processing Zone (EPZ) of Caceres, in the state Mato Grosso, Brazil. Documentary survey on official websites and bibliographical research on the subject were carried out. It was found that the EPZ emerge as a locational strategy in view of the role of the General Production Conditions (GPC) and are used as an instrument of industrial economic policy. Furthermore, the GPC reappear as discursive material and symbolic support for the regional elites, nongovernmental entities, public managers linked to the three scales of public administration (municipal, state, and federal) and parliamentarians (council members, deputies and, senators). Thus, a developmentalist political and ideological practice has been built through the implementation of the EPZ in Caceres, Mato Grosso.
Keywords: development; export processing zone (EPZ); Caceres; regional elites